Re-defining Modernity and Development Dimension in Quest of Indigenous and Ingenuous Prosperity of Himalayan Region - Dahal, Atindra (Technium Social Sciences Journal, 2020)
At this time, all the countries around the globe- regardless of size, location, political variation and differences of the past legacies- are actively engaged and have incessantly exhibited a deep penchant into discourse of development. This article tries to path find the most acceptable notion of development along with demarcation of Himalayan region. Furtherance, this writing explores way-out for the very region’s development by evidently detaining and vanquishing the existing hindrances and noticeable hurdles, which have often plunged and forged the profound prospects of sound organic developmental gain regularly towards a dauntingly downward trajectory since long.